2018
DOI: 10.1002/cbic.201700686
|View full text |Cite
|
Sign up to set email alerts
|

Dual Labeling of the CBP/p300 KIX Domain for 19F NMR Leads to Identification of a New Small‐Molecule Binding Site

Abstract: Protein-Observed Fluorine NMR (PrOF NMR) spectroscopy is an emerging technique for screening and characterizing small-molecule-protein interactions. The choice of which amino acid to label for PrOF NMR can be critical for analysis. Here we report the first use of a protein containing two different fluoroaromatic amino acids for NMR studies. Using the KIX domain of the CBP/p300 as a model system, we examine ligand binding of several small-molecule compounds elaborated from our previous fragment screen and ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…An elegant combination of X-ray crystallography, NMR spectroscopy, and MD simulations has been recently applied to unravel the distribution of conformational states along the reaction pathway of a homodimeric enzyme 22 . Pomerantz and co-workers have successfully utilized fluoroaromatic amino acids for the implementation into proteins to report on the structure-activity relationship 23 focusing on screening of small molecule-protein interactions based on protein-observed fluorine NMR spectroscopy 24 . Moreover, incorporation of difluorotyrosine has been successfully employed enabling to report on tyrosine phosphorylation 25 or to probe distinct conformational states of a protein which are related to signalling by applying 19 F NMR spectroscopy 26 .…”
mentioning
confidence: 99%
“…An elegant combination of X-ray crystallography, NMR spectroscopy, and MD simulations has been recently applied to unravel the distribution of conformational states along the reaction pathway of a homodimeric enzyme 22 . Pomerantz and co-workers have successfully utilized fluoroaromatic amino acids for the implementation into proteins to report on the structure-activity relationship 23 focusing on screening of small molecule-protein interactions based on protein-observed fluorine NMR spectroscopy 24 . Moreover, incorporation of difluorotyrosine has been successfully employed enabling to report on tyrosine phosphorylation 25 or to probe distinct conformational states of a protein which are related to signalling by applying 19 F NMR spectroscopy 26 .…”
mentioning
confidence: 99%
“…Subsequent studies using more elaborated fragments and a dually labeled KIX protein with 3FY and 4-fluorophenylalanine (4FF) at F612, further elucidated the binding site to be near, but distinct from the MLL binding site. 118 This result was important as it indicated that the KIX domain could be targeted without competing against endogenous transcription factor interactions.…”
Section: Protein-observed 19 F Nmrmentioning
confidence: 99%
“…We have since shown that two fluorinated amino acids can be incorporated simultaneously for better coverage of the MLLbinding site (Figure 2A,B). 44 Prior research showed transcription factors bind to KIX through two distinct binding sites and potentiate binding affinities for ternary complex formation ∼2-fold in most cases, 39 but as high as 20-fold in others. 45 NMR analysis has focused on the backbone amides and aliphatic side chains.…”
Section: Kix Ppi Analysis By Prof Nmrmentioning
confidence: 99%
“…An unexpected finding using 4FF/3FY dual-labeled-KIX revealed one of the fragments binding to a third site near Y631 on the protein. 44 Using PrOF NMR, 1 H− 15 N-HSQC NMR, in-silico solvent mapping, and small molecule docking, we identified a previously uncharacterized small molecule binding site with an elaborated fragment 2 (K d = 740 μM, Figure 2D) and KG-501, 43 a known CREB-KIX inhibitor of moderate affinity (K d = 115 μM). This new binding site offers the potential to negatively regulate transcription factor binding without competing with native PPIs.…”
Section: Kix Ppi Analysis By Prof Nmrmentioning
confidence: 99%
See 1 more Smart Citation